Predictors of Persistence of Anxiety, Hyperarousal Stress, and Resilience During the COVID-19 Epidemic: A National Study in Iran - Sharif Nia, Hamid; Akhlaghi, Elham; Torkian, Samaneh; Khosravi, Vahid; Etesami, Reza; Froelicher, Erika Sivarajan; Pahlevan Sharif, Saeed (Frontiers in Psychology, 2021)
Background: The coronavirus pandemic can cause unprecedented global anxiety, and, in contrast, resilience can help the mental health of people in stressful situations. This study aimed to assess anxiety, hyperarousal stress, the resilience of the Iranian population, and their related factors during the coronavirus disease 2019 (COVID-19) epidemic. Methods: A cross-sectional study was conducted in 31 provinces in Iran between March 18 and 25, 2020. A four-part questionnaire, including the demographic information, the State-Trait Anxiety Inventory (STAI-y1—a 20-item standard questionnaire for obvious anxiety), the Connor–Davidson Resilience Scale (CD-RISC—a 25 item standard questionnaire), and the stress hyperarousal subscale from the Impact of Event Scale-Revised (IES-R), was used to collect data. The ordinal multivariable generalized estimating equation (GEE) model was used to identify correlates of the psychological factors mentioned above. The Fisher exact test was used to investigate the relationship between anxiety, stress, resilience, and the COVID-19 outbreak. All analyses were conducted with SPSS 26 and GIS 10.71. Results: The findings show that most people had moderate-to-severe anxiety (80.17%) and a high level of resilience (96.4%) during the COVID-19 epidemic. The majority of participants had a moderate level of stress (58.9%). The lowest and highest prevalences of psychiatric disorders were in Sistan and Baluchestan (3.14 cases per 100,000 people) and Semnan (75.9 cases per 100,000 people) provinces, respectively. Men and unmarried people were the only variables significantly associated with anxiety and resilience. Age, gender, and education were significantly associated with hyperarousal stress. Conclusion: The high and moderate levels of anxiety and stress in Iranians can have negative effects on the well-being and performance of the people and can lead to serious problems. Also, high resilience during negative life events (such as the COVID-19 pandemic) is associated with the well-being in the lives of people. The results of this study can be used in interventions and other psychological studies.